The attitudes of staff members at the Cape Peninsula University of Technology towards the start of an HIV/AIDS workplace peer education programme - Hoffman, Lorraine Elizabeth (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2011.